2019
DOI: 10.1038/s41467-019-10808-7
|View full text |Cite|
|
Sign up to set email alerts
|

Association of imputed prostate cancer transcriptome with disease risk reveals novel mechanisms

Abstract: Here we train cis -regulatory models of prostate tissue gene expression and impute expression transcriptome-wide for 233,955 European ancestry men (14,616 prostate cancer (PrCa) cases, 219,339 controls) from two large cohorts. Among 12,014 genes evaluated in the UK Biobank, we identify 38 associated with PrCa, many replicating in the Kaiser Permanente RPGEH. We report the association of elevated TMPRSS2 expression with increased PrCa risk (independent of a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…Investigation by CCLE demonstrated higher levels of TMPRSS2 expression in several cell lines such as prostate, colorectal, stomach and bile duct in comparison with other cell lines. These findings were supported by studies conducted on prostate cancer patients that showed higher levels of TMPRSS2 expression in comparison with normal subjects (Emami et al, 2019). Also, results from an investigation of Tmprss2 expression in mice showed that Tmprss2 was considerably expressed in epithelia of the gastrointestinal, urogenital and respiratory tracts (Vaarala et al, 2001).…”
Section: Discussionmentioning
confidence: 66%
“…Investigation by CCLE demonstrated higher levels of TMPRSS2 expression in several cell lines such as prostate, colorectal, stomach and bile duct in comparison with other cell lines. These findings were supported by studies conducted on prostate cancer patients that showed higher levels of TMPRSS2 expression in comparison with normal subjects (Emami et al, 2019). Also, results from an investigation of Tmprss2 expression in mice showed that Tmprss2 was considerably expressed in epithelia of the gastrointestinal, urogenital and respiratory tracts (Vaarala et al, 2001).…”
Section: Discussionmentioning
confidence: 66%
“…It is worth noting that based on the predicted DNA methylation-PrCa risk, DNA methylation-gene expression, and predicted gene expression-PrCa risk results, we also observed six CpG sites and four genes (VAMP8, C4B, BAIAP2L1, and NCOA4) with inconsistent directions of association for the DNA methylation-gene expression-PrCa pathway (Supplementary Table 7). Of these genes, NCOA4, BAIAP2L1, and VAMP8 are candidate PrCa susceptibility genes identified in earlier TWAS 27,29,30 . Future work is needed to better understand these associations.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, p53 activation induced both FTH and FTL expression in human lung cancer cells [155]. NCOA4, which is responsible for ferritin degradation and cytosolic iron increase, was found overexpressed in transformed endometriotic cells and pancreatic cancer cell lines and correlated to prostate cancer risk [206][207][208]. Furthermore, inactivation of p53 and activation of transforming protein p21 (HRAS) and proto-oncogene MYC led to overexpressed NCOA4 [206].…”
Section: Cellular Iron Dysregulation In Cancermentioning
confidence: 99%